ŞEKİL HATIRLATMALI CU-%13, AL-%4Nİ VE CU%13, 5AL-%4Nİ ALAŞIMLARININ TERMAL ÖZELLİKLERİNİN İNCELENMESİ - USLU, YAVUZ (Fırat Üniveristesi, 2003)
Bu çalışmada, Şekil Hatırlamalı Cu-%13Al-%4Ni ve Cu-%t3,5Al-%4Ni Alaşımlarının Termal Özellikleri incelendi. Bu alaşımlar ana fazda DO3, martensit fazda uzun periyodu 18R yapılara sahiptir. Şekil hatırlamalı CuAlNi alaşımlarına uygulanan dört farklı ısıl işlemin, numuneler üzerindeki etkileri incelendi. Bu çalışmada diferansiyel tarama kalorimetresi (DSC), x- ışın difraksiyonu, geçirmeli elektron mikroskobu ve optik mikroskop teknikleri kullanıldı. Farklı ısıl işlemlerin; şekil hatırlama, kristalografı, morfoloji ve faz dönüşüm sıcaklıkları üzerinde bazı farklı etkilere sebep olduğu gözlendi. Özellikle farklı termal uygulamalar ve konfigürasyonların, numunelerin kristalografik örgü parametrelerini ve dönüşüm sıcaklıklarını etkilediği gözlemlendi ve bütün numunelerin austenit fazda düzenli bir yapıya, martensit fazda M 1 8R monoklinik yapıya sahip oldukları belirlendi. Anahtar Kelimeler : CuAlNi alaşımları, şekil hatırlama, termoelastik martensitik dönüşüm, ısıl işlem, dönüşüm sıcaklığı, süper örgü.

In this study, Thermal Properties of Shape Memory Cu-%13Al-%4 Ni and Cu-%13,5 Al- %4 Ni Alloys have been investigated. These alloys have D03 and long period 18R structures at austenit phase and martensite phase, respectively. Four differents types of thermal processes have been applied on the shape memory CuAINi alloys. The effects of these thermal processes on the samples have been investigated. Differential scanning calorimetry (DSC), x-ray diffraction, transmission electron microscope and optical microscope tecniques have been used in this study. It has been observed that the different thermal processes cause some different effects on the shape memory, crystalography, morphology and transformation temperatures of phases. Especially, different thermal applications and configrations effected the transformation themperatures and crystalographic lattice parameters of the specimens and it was calculated that all of the samples have an ordered structure at the austenit phase and M18R monoclinic structure at the martensit phase. Keywords: CuAINi alloys, shape memory effect, thermoelastic martensitic transformation, thermal process, transformation themperature, super lattice.
An investigation of thermal properties of shape memory Cu-%13, Al-%4Ni and Cu%13, 5Al-%4Ni
Keywords: Fizik ve Fizik Mühendisliği; Physics and Physics Engineering